Odpowiedź :
Odpowiedź:
( √2 x +1)²=2(x²+x+1)
2 x²+ 2√2 x +1=2x²+2x+2
2√2 x - 2x= 2-1
(2√2 -2 )x= 1
x= 1/(2√2-2)
x= (2√2+2)/(2√2-2)(2√2+2)
x= (2√2+2)/ (8-4)
x= 2(√2+1)/4
x= (√2+1)/2
x= 1/2 (√2+1) odp. B
Szczegółowe wyjaśnienie:
Odpowiedź:
[tex](\sqrt{2}x+1)^2=2(x^2+x+1)\\\\(\sqrt{2}x)^2+2\sqrt{2}x\cdot1+1^2=2x^2+2x+2\\\\2x^2+2\sqrt{2}x+1=2x^2+2x+2\\\\\not2x^2+2\sqrt{2}x-\not2x^2-2x=2-1\\\\2\sqrt{2}x-2x=1\\\\(2\sqrt{2}-2)x=1\ \ |:(2\sqrt{2}-2)\\\\x=\frac{1}{2\sqrt{2}-2}\\\\x=\frac{1}{2\sqrt{2}-2}\cdot\frac{2\sqrt{2}+2}{2\sqrt{2}+2}\\\\x=\frac{2\sqrt{2}+2}{(2\sqrt{2}-2)(2\sqrt{2}+2)}\\\\x=\frac{2\sqrt{2}+2}{(2\sqrt{2})^2-2^2}\\\\x=\frac{2\sqrt{2}+2}{4\cdot2-4}\\\\x=\frac{2\sqrt{2}+2}{8-4}\\\\x=\frac{\not2^1(\sqrt{2}+1)}{\not4_{2}}[/tex]
[tex]x=\frac{1}{2}(\sqrt{2}+1)\\\\\\Odp.B[/tex]